THE ROLE OF RESPONSIBILITY ACCOUNTING IN ENHANCING FINANCIAL TRANSPARENCY AND ACCOUNTABILITY: EVIDENCE FROM PT BANK RAKYAT INDONESIA (PERSERO) TBK - Shabita Nuria Zahra; Gracia Chrisma Putri Kusuma; Aulia Wulandari; Fitri Puspita Ningrum; Maulana Rozak Saputra (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2025)
Responsibility accounting has become an essential managerial control system for enhancing financial transparency, accountability, and organizational performance, particularly within the banking sector where effective financial governance is critical. Although previous studies have examined the relationship between responsibility accounting and managerial performance, limited empirical evidence has specifically investigated its role in simultaneously strengthening financial transparency and accountability in Indonesia's state-owned banking institutions. Therefore, this study aims to analyze the implementation of responsibility accounting at PT Bank Rakyat Indonesia (Persero) Tbk and evaluate its contribution to transparent financial management and accountable corporate governance. This study employed a qualitative descriptive approach using secondary data collected through documentation of the Company's audited Annual Reports for 2023 and 2024, supported by relevant academic literature. The analysis focused on comparing budgeted and actual expenditures, evaluating budget realization, and assessing financial performance using Return on Assets (ROA) and Return on Investment (ROI) as complementary indicators of managerial effectiveness. The findings reveal that responsibility accounting has been effectively implemented, as reflected by high budget utilization rates of 97.60% in 2023 and 97.31% in 2024, stable profitability, consistent ROA performance, and only a marginal decline in ROI. These results indicate effective budgetary control, efficient resource allocation, disciplined financial management, and strengthened managerial accountability. Furthermore, the implementation of responsibility accounting enhances financial transparency by providing systematic financial reporting that supports informed decision-making and reinforces good corporate governance. This study contributes to the management accounting literature by providing empirical evidence of the strategic role of responsibility accounting in improving financial governance within Indonesia's banking industry. Practically, the findings offer valuable insights for financial institutions seeking to strengthen accountability, transparency, and sustainable organizational performance through responsibility-based management systems.